Nepal : Operational Issues and Prioritization of Resources in the Health Sector - World Bank (Washington, DC, 2013)
This study is the first comprehensive analysis of health care delivery in Nepal, and fills major gaps on the knowledge of the country's health sector, expanding the understanding of current, and prospective causes of sickness and death, of the actual level of external assistance in the sector, and of the level of additional resources needed to meet basic needs, and ease institutional constraints within health services. It is suggested that large projected increases in the population will place enormous pressure on the already strained resources, while regional disparities in health indicators, and care are large, and under-served. Although policymakers should still deal with infectious diseases, and related illnesses, special attention should be devoted to improve the health status of children, and target the disadvantaged, and poorer areas. Furthermore, the study implies that institutional weaknesses, and ineffective program management are at the root of poor service delivery. Recommendations suggest an increased political commitment, focusing on infectious diseases, maternal, and prenatal ailments, and nutrition deficiencies. In addition, institutional capacity should be developed, and better health care systems ensured through public-private partnerships. Priorities should be established through careful planning, appropriate management, and financial availability.